Tıbbi Müdahalelerde Aydınlatılmış Onamın Hukuki Niteliği ve Gelişen Teknolojiler ile Sürecin İyileştirilmesi - Uzun, Remzi Çağrı (My University, 2025)
Bu tezde, tıbbi müdahalelerde hastanın bilgilendirilmiş rızasını ifade eden 'aydınlatılmış onam' kavramının hukuki niteliği çok boyutlu biçimde ele alınmıştır. Özellikle Türk Hukukunda, tıbbi müdahalenin hukuka uygun sayılabilmesi için aranan dört temel koşuldan biri olan onam, yalnızca teknik bir prosedür değil, bireyin temel hak ve özgürlüklerinin korunması açısından da kritik öneme sahiptir. Tez kapsamında, aydınlatılmış onamın tarihsel gelişimi, hukuki dayanakları, şekli ve kapsamı ayrıntılı olarak incelenmiş; bu süreçte hekimlerin sorumluluğuna ilişkin yargı kararlarına da yer verilmiştir. Bununla birlikte, teknolojinin gelişimiyle birlikte tıbbi müdahalelerde onam sürecinin nasıl daha etkili hale getirilebileceği değerlendirilmiştir. Multimedya destekli bilgilendirme yöntemleri ve kişiselleştirilmiş risk hesaplama araçlarının onam sürecine entegrasyonu, hem hasta anlayışını hem de hukuki korumayı güçlendiren bir dönüşüm olarak sunulmuştur. Elde edilen bulgular doğrultusunda, yalnızca hukuki değil, etik ve pratik boyutları da dikkate alan bütüncül bir onam sisteminin gerekliliği ortaya konulmuştur.

This thesis addresses the legal nature of informed consent in medical interventions and examines how emerging technologies can improve this process. In Turkish law, the legality of a medical intervention depends on four key conditions: it must be performed by authorized individuals, have a legitimate purpose, comply with current medical standards, and be based on the informed consent of the patient. If any of these conditions are not met, the intervention becomes unlawful and may lead to criminal, civil, or administrative liability for the physician. The study thoroughly explores the historical development, legal foundations, formal requirements, and scope of informed consent. It also reviews judicial decisions regarding the responsibilities of physicians in this context. Furthermore, the study evaluates how new technologies, such as multimedia-supported communication methods and personalized risk assessment tools, can enhance the effectiveness and clarity of the consent process. The findings highlight the necessity of a comprehensive informed consent framework that addresses legal, ethical, and practical dimensions to ensure both patient protection and professional accountability.
Informed Consent in Medical Interventions and Its Legal Framework in the Context of Emerging Technologies
Keywords: Hukuk; Law